Evaluating Technopark Service Quality Using The Carter Model And Importance-Performance Analysis (IPA) - Telma Anis Safitri; Katon Muhammad; Zakiyyan Zain Alkaf (Faculty of Economics and Business Universitas Jenderal Soedirman, 2026)
Technoparks play a pivotal role in fostering regional innovation; however, many in Indonesia face significant challenges, including underutilized facilities and inconsistent service quality, which constrain their overall effectiveness. This study aims to evaluate and enhance the service quality of Technoparks in Java—specifically in Solo, Bandung, and Pekalongan—by implementing the CARTER model, which assesses six dimensions: Compliance, Assurance, Reliability, Tangibles, Empathy, and Responsiveness. A quantitative approach was employed, integrating the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA), further enriched by spatial mapping. The findings reveal varying levels of visitor satisfaction across the locations. Pekalongan Technopark achieved the highest CSI score of 87.41% (